Killing us slowly: Pre‐empting suicide at a women’s hostel in Chennai - Krishnan, S (Wiley, 2019)
This paper draws on ethnographic research in Chennai to unpack the pre-emptive logic that shapes anti-suicide interventions at hostels—dormitories—for college-going women in this city. Its central contention is that a concern for the production of a presumed future becomes, in hostels, a governmental technology that is used to limit young women’s lifeworlds in the present. These regimes of intervention reinforce the unliveability of attachments, intimacies and affects that popular discourse and scaled-up demographic narrative associate with the potential for suicide. Building from this, the paper also shows that such regimes engender feelings of suffocation and attrition among the young women who live in hostels. “Being slowly killed”, as they call it, draws attention to suicide not as a spectacular event but as a site where the terms of everyday life are remade.